Prognostic impact of electrocardiographic left ventricular hypertrophy following transcatheter aortic valve replacement. Issue 4 (April 2021) - Tanaka, Tetsu; Yahagi, Kazuyuki; Asami, Masahiko; Ninomiya, Kai; Kikushima, Hosei; Okuno, Taishi; Horiuchi, Yu; Yuzawa, Hitomi; Komiyama, Kota; Tanaka, Jun; Yokozuka, Motoi; Miura, Sumio; et al.
Highlight: Electrocardiographic (ECG) criteria of left ventricular hypertrophy (LVH) are known. We evaluated the impact of ECG LVH on transcatheter aortic valve replacement (TAVR). ECG LVH was related to a lower incidence of adverse events within 1 year after TAVR. ECG LVH was associated with greater LV mass index regression following TAVR. The findings showed importance of ECG assessment for LVH in patients undergoing TAVR. Abstract: Background: Left ventricular hypertrophy (LVH) develops with both structural and electrical remodeling in response to elevated afterload due to aortic stenosis (AS). This study evaluated the prognostic value of electrocardiographic LVH (ECG LVH) after transcatheter aortic valve replacement (TAVR). Methods: A retrospective study including 157 consecutive patients who underwent TAVR was conducted. ECG LVH was defined as Sokolow–Lyon voltage (S in V1 + R in V5/6 ) before TAVR was ≥3.5mV. We investigated the association between ECG LVH and the 1-year composite outcome comprising all-cause death and rehospitalization related to heart failure. ECG and echocardiographic measurements at 1, 6, and 12 months after TAVR were assessed. Results: The baseline characteristics were comparable between the ECG LVH (n = 74) and non-ECG LVH groups (n = 83). The ECG LVH was associated with a significantly greater reduction of Sokolow–Lyon voltage and LV mass index than the non-ECG LVH after TAVR. The absence of ECG LVH was an independent predictor of the 1-year composite outcome [adjusted hazard ratio (HR), 2.27; 95% confidence interval (CI), 1.01 – 5.60; p = 0.04]. Furthermore, a reduction of Sokolow–Lyon voltage from baseline to 1-month follow-up, but not a reduction of LV mass index, was associated with a lower cumulative composite outcome from 1 month to 1 year (adjusted HR, 0.36; 95% CI, 0.15 – 0.86; p = 0.02). Conclusions: ECG LVH was associated with a low incidence of adverse clinical outcomes and greater reverse LV remodeling after TAVR. Preprocedural and serial LVH assessment by ECG might be useful in AS patients undergoing TAVR.